2014
DOI: 10.1371/journal.pone.0107021
|View full text |Cite
|
Sign up to set email alerts
|

Population Specific Impact of Genetic Variants in KCNJ11 Gene to Type 2 Diabetes: A Case-Control and Meta-Analysis Study

Abstract: Background and ObjectivesPotassium inwardly rectifying channel, subfamily J, member 11 (KCNJ11) gene have a key role in insulin secretion and is of substantial interest as a candidate gene for type 2 diabetes (T2D). The current work was performed to delineate the genetic influence of KCNJ11 polymorphisms on risk of T2D in South Indian population through case-control association study along with systematic review and meta-analysis.MethodsA case-control study of 400 T2D cases and controls of South Indian origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
1
24
1
Order By: Relevance
“…Fourteen of the novel BP variants identified in the present study reside in loci that were previously reported in GWAS to be associated with lipids 19 , immunologic diseases 2022 , and metabolic phenotypes 2325, 29 (Table 2 and Supplementary Table 7). Thirteen of the previously identified BP variants were also linked to non-BP traits/diseases (Supplementary Table 19).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Fourteen of the novel BP variants identified in the present study reside in loci that were previously reported in GWAS to be associated with lipids 19 , immunologic diseases 2022 , and metabolic phenotypes 2325, 29 (Table 2 and Supplementary Table 7). Thirteen of the previously identified BP variants were also linked to non-BP traits/diseases (Supplementary Table 19).…”
Section: Discussionmentioning
confidence: 77%
“…Of the 28 newly identified common variants for BP, 14 were genome-wide significant in prior GWAS of lipids 19 , immunologic disease 2022 , diabetes 2325 , kidney function 26 , age at menarche 27 , resting heart rate 28 , waist-hip ratio 29 , and homocysteine concentration 30 , but not BP (Table 2 and Supplementary Table 7). Six additional variants were reported for several phenotypes (Table 2) in previous candidate gene, patent filing or GWAS studies, but their P values were not specified or did not reach the genome-wide significance level 3136 .…”
Section: New Loci Associated With Bp By Single Variant Analysesmentioning
confidence: 99%
“…KCNJ11 , encoding a member of the potassium channel gene family, contributes to insulin secretion. Previous reports showed that rs5215 is associated with the development of type 2 diabetes mellitus. High mobility group protein 20A ( HMG20A ) was related to the development of type 2 diabetes mellitus in European individuals, and it might contribute to insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Increased numbers of patients in study populations have revealed an association between this polymorphic marker and the T2DM development [31][32][33][34][35][36][37]. Despite the fact that this association was found by other investigators [38], the K23 allele has been associated with the increased risk gene expression [11].…”
Section: Discussionmentioning
confidence: 99%